2015
DOI: 10.1245/s10434-015-4918-0
|View full text |Cite
|
Sign up to set email alerts
|

Can Routine Imaging After Neoadjuvant Chemotherapy in Breast Cancer Predict Pathologic Complete Response?

Abstract: Neither MRI nor MGR or US can diagnose a pCR (ypT0) with sufficient accuracy to replace pathologic diagnosis of the surgical excision specimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
56
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 25 publications
2
56
1
6
Order By: Relevance
“…Our trial revealed a poor NPV for CBE (46.2% in TNBC); thus a CBE evaluation may be a poor indicator of when to order an MRI for the patient during NACT. One study reported a NPV of 61.5% in TNBC patients by MG, as well as a NPV of 57.9% in TNBC patients by US, which is superior to the CBE NPV found in our study for this subtype (15).…”
Section: Figure 2 Positive Predictive Value (Ppv) (A) and False-posicontrasting
confidence: 87%
See 2 more Smart Citations
“…Our trial revealed a poor NPV for CBE (46.2% in TNBC); thus a CBE evaluation may be a poor indicator of when to order an MRI for the patient during NACT. One study reported a NPV of 61.5% in TNBC patients by MG, as well as a NPV of 57.9% in TNBC patients by US, which is superior to the CBE NPV found in our study for this subtype (15).…”
Section: Figure 2 Positive Predictive Value (Ppv) (A) and False-posicontrasting
confidence: 87%
“…It is established that high rates of pCR are achieved in the TNBC subtype in comparison to HR+ subtypes (10) well as a 0% FNR in TNBC (15). Our study also reveals a 4/4 (100%) NPV and 0/11 (0%) FNR by imaging in the TNBC subset.…”
Section: Figure 2 Positive Predictive Value (Ppv) (A) and False-posisupporting
confidence: 61%
See 1 more Smart Citation
“…Conventional imaging modalities, such as mammography and breast ultrasound, have limited accuracy in predicting pCR, [2][3][4] but this improves with addition of breast magnetic resonance imaging (MRI). [5][6][7][8][9][10] However, even with trimodality imaging (mammogram, ultrasound, and MRI), the negative predictive value for pCR is generally under 90%, [9][10][11] leading to the conclusion that neither breast MRI nor mammogram or breast ultrasound can preoperatively identify pCR with sufficient accuracy to replace pathologic diagnosis of the surgical excision specimen. 9 Recently, interest has developed in evaluating imageguided biopsy of the tumor bed in order to enhance the accuracy of predicting pCR in patients who have clinically complete and radiologically complete/near-complete response to NAC.…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10] However, even with trimodality imaging (mammogram, ultrasound, and MRI), the negative predictive value for pCR is generally under 90%, [9][10][11] leading to the conclusion that neither breast MRI nor mammogram or breast ultrasound can preoperatively identify pCR with sufficient accuracy to replace pathologic diagnosis of the surgical excision specimen. 9 Recently, interest has developed in evaluating imageguided biopsy of the tumor bed in order to enhance the accuracy of predicting pCR in patients who have clinically complete and radiologically complete/near-complete response to NAC. This approach has the potential to more accurately identify optimal candidates for possible omission of primary tumor surgical excision for patients who intend to be treated with breast-conserving therapy.…”
mentioning
confidence: 99%